Are the poorest families really who belong to the Familias en Acción program? (2018)
The development of social programs that benefit the population in conditions of poverty and vulnerability in Colombia such as Familias en Acción has made great strides in eradicating extreme poverty in the country, but it has structural flaws that suggest the need to rethink the way they are targeted and the minimum permanency requirements of the families that benefit from the subsidy so that those who are part of the program are actually the target population and need the help provided by the government.